How resilient is mortgage credit supply? Evidence from the COVID-19 pandemic - Andreas Fuster; Aurel Hizmo; Lauren Lambie-Hanson; James Vickery; Paul Willen (Federal Reserve Bank of Boston, 2021)
We study the evolution of US mortgage credit supply during the COVID-19 pandemic. Although the mortgage market experienced a historic boom in 2020, we show there was also a large and sustained increase in intermediation markups that limited the pass-through of low rates to borrowers. Markups typically rise during periods of peak demand, but this historical relationship explains only part of the large increase during the pandemic. We present evidence that pandemic-related labor market frictions and operational bottlenecks contributed to unusually inelastic credit supply, and that technology-based lenders, likely less constrained by these frictions, gained market share. Rising forbearance and default risk did not significantly affect rates on "plain-vanilla" conforming mortgages, but it did lead to higher spreads on mortgages without government guarantees and loans to the riskiest borrowers. Mortgagebacked securities purchases by the Federal Reserve also supported the flow of credit in the conforming segment.
Keywords: G21; G23; G28; 330; mortgage; credit; financial intermediation; fintech; COVID-19